Enhancement of math content accessibility in EPUB3 educational publications. Issue 1 (3rd April 2019) - Brzostek-Pawłowska, Jolanta; Rubin, Małgorzata; Salamończyk, Andrzej
ABSTRACT: The article presents methods of increasing mathematical content accessibility in educational e-publications using multimodal user interfaces (UI). Educational mathematical publications such as exercise notebooks and worksheets, require student's interactivity in problem solving. EPUB3, an open format for e-publications, has the possibilities of creating multimedia, interactive mathematics content. Among the programs that support EPUB3, only a few support the MathML format presenting formulas, and provides limited possibilities for user interactivity, insufficient in mathematical education. Our solutions in the PlatMat system increase the interactive accessibility of EPUB3 mathematical content for students with visual impairment. The solutions are based on concurrent multimodal alternative interfaces for exploring math content in EPUB3 publications. Students can read and modify formulas choosing preferred UI and device. Similarly, in different modes (visual, acoustic and touch) students can recognise function graphs and shapes of geometrical figures saved in scalable vector graphics (SVG) format. Teachers can create universal mathematical documents for all students. The system supports inclusive maths education and is designed according to the principles of universal design for learning (UDL). The article describes the system's usefulness in relation to research conducted among maths teachers. Positive results have become the basis for the further development of the system.